War and Nature: The Environmental Consequences of War in a Globalized World - Brauer, Jurgen (Rowman & Littlefield Publishers, 2009)
The inherent dangers of war zones constrain even the most ardent researchers, with the consequence that little has been known for certain about the effects of war on stable environments. War and Nature sifts through the available data from past wars to evaluate the actual impact that combat has on natural surroundings. Examining conflicts of various kinds_he long war in tropical Vietnam, the relatively brief and highly technical wars in the Persian Gulf, and various civil wars in Africa and South-Central Asia fought with small arms_Brauer asks whether differences in technology, location, and duration are critical in causing environmental and humanitarian harm. A number of unexpected conclusions are drawn from this data, including practical agendas for collecting scientific evidence in future wars and suggestions about what the world's environmental and conservation organizations can do. One thing War and Nature does is to show us how globalization can be a force harnessed for good ends.